EFFECT OF FEED SUPLEMENTATION TO KING GRASS BASAL FEED ON PERFORMANCE OF BLIGON GOAT RAISED BY WOMEN FARMER GROUP AT KWARASAN, NGLIPAR, GUNUNGKIDUL - Kustantinah, Kustantinah; Hartadi, Hari; Irwansyah, Rohman Sholeh (2007)
Research was conducted to evaluate performance of Bligon goats at village condition for 3 months. THirty animals consisted of 5 males and 5 females. The groups were fed chopped King grass as basal diet; the first group (K) received no supplement, while the second group (P1) received protein supplement and the third group (P2) received energy supplement. Data collected were individual feed consumption and feces excretion and live weight of the animals (LW). Samples of feeds and feces were analyzed for proximate and fiber components. Data collected were than satisticaly analyzed based on factorial design, using sex and supplementation as factors. The results indicated that supplementation improved (P<0.05) consumption of DM, OM, CP, NDF and ADF, digestibility of OM, and CP, and LW of animals. The research concluded that supplementation of protein feed on grass basal diet for goats during dry season is suggested.